«Nelle scuole delli religiosi e alle disputazioni delli filosofanti». Approach to the problem of Dante’s cultural formation - Valastro Canale, Angelo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This article aims to offer the reader a panoramic view of the main critical acquisitions concerning the youthful formation of Dante Alighieri. After seven centuries of study, the sources from which the future author of the Commedia drew are still largely conjectural, although recent archival analyses and ongoing research projects have broadened our horizons of knowledge.